Serum soluble mesothelin-related protein (SMRP) and fibulin-3 levels correlate with baseline malignant pleural mesothelioma (MPM) tumor volumes but are not useful as biomarkers of response in an immunotherapy trial. (April 2021) - Katz, Sharyn I.; Roshkovan, Leonid; Berger, Ian; Friedberg, Joseph S.; Alley, Evan W.; Simone, Charles B.; Haas, Andrew R.; Cengel, Keith A.; Sterman, Daniel H.; Albelda, Steven M.
Highlights: Serum soluble mesothelin-related protein (SMRP) and fibulin-3 are possible MPM biomarkers. SMRP and fibulin-3 serological levels correlated with initial tumor volumes. SMRP and fibulin-3 longitudinal serological levels are not useful for immunotherapy response. Abstract: Objectives: Soluble mesothelin-related protein (SMRP) and fibulin-3 serum levels may serve as diagnostic and prognostic biomarkers of malignant pleural mesothelioma (MPM). Here, we evaluate these markers for correlation to tumor volume, prognosis and response assessment in a clinical trial of immunogene therapy in combination with chemotherapy. Materials and methods: Serial serum levels of SMRP and fibulin-3 were measured in adult patients with biopsy-proven MPM enrolled in two prospective clinical trials. Pre-therapy computed tomography (CT) measurements of tumor burden were calculated and correlated with pre-therapy serum SMRP and fibulin-3 levels in these two trials. Serological data were also correlated with radiological assessment of response using Modified RECIST criteria over the first 6 months of intrapleural delivery of adenovirus-IFN alpha (Ad.IFN-α) combined with chemotherapy. Results: A cohort of 58 patients who enrolled in either a photodynamic therapy trial or immunotherapy clinical trial had available imaging and SMRP serological data for analysis of whom 45 patients had serological fibulin-3 data. The cohort mean total tumor volume was 387 cm 3 (STD 561 cm 3 ). Serum SMRP was detectable in 57 of 58 patients (mean 3.8 nM, STD 6.0). Serum fibulin-3 was detected in 44 of 45 patients (mean 23 ng/mL, STD 14). At pre-therapy baseline in these two trials, there was a strong correlation between tumor volume and serum SMRP levels (r = 0.61, p < 0.001), and a moderate correlation between tumor volume and serum fibulin-3 levels (r = 0.36, p = 0.014). Twenty-eight patients in the immunotherapy trial had longitudinal serologic and radiographic data. Fold-changes in SMRP and fibulin-3 did not show significant correlations with modified RECIST measurements. Conclusions: Although our data show correlations of SMRP and fibulin-3 with initial tumor volumes as measured by CT scanning, the use of SMRP and fibulin-3 as serological biomarkers in the immunotherapy trial were not useful in following tumor response longitudinally.